2008
DOI: 10.1097/01.ncc.0000305751.28120.f4
|View full text |Cite
|
Sign up to set email alerts
|

The Lived Experience of Lebanese Family Caregivers of Cancer Patients

Abstract: The purpose of this study was to explore, through in-depth semistructured interviews, the lived experience of Lebanese family caregivers of cancer patients and acquire a better knowledge of the meaning and interpretation of their experience. The study design was based on the Utrecht School of Phenomenology. This study followed purposeful sampling, in which 9 participants with a mean age of 51 years were selected. Data were analyzed using the hermeneutic phenomenological approach based on the Utrecht School of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 42 publications
5
39
0
Order By: Relevance
“…[33] A finding that concurs with Doumit et al's [20] Arabic study which addressed the lived experience of Lebanese family caregivers of cancer patients, which showed that carers lived in a state of emergency filled with fears and uncertainty of what may occur to the ill person at any time. Similarly to the caregivers in this study, Lebanese caregivers appeared to share the pain of their loved ones.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…[33] A finding that concurs with Doumit et al's [20] Arabic study which addressed the lived experience of Lebanese family caregivers of cancer patients, which showed that carers lived in a state of emergency filled with fears and uncertainty of what may occur to the ill person at any time. Similarly to the caregivers in this study, Lebanese caregivers appeared to share the pain of their loved ones.…”
Section: Discussionsupporting
confidence: 73%
“…A finding that relates to caregivers lack of preparedness and feelings of fear, anxiety, stress, inadequacy and uncertainty about their ability of providing home care. [20,[35][36][37][38][39] Furthermore, the literature affirmed that there was no discussion about what to expect in palliative home care and carers felt health professionals were hesitant to discuss difficult issues like managing palliative care at home and end of life care. [40] Thus, they learned caregiving skills by trial and error.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This led to feelings of isolation in the person with cancer, and prevented the sense of sharing and getting through together. Doumit et al (2008) described how the situation could also be the opposite, where in other socio-cultural contexts the person with cancer might have less knowledge about the disease and its prognosis than the caregiver and that having more knowledge was experienced as a burden.…”
Section: Discussionmentioning
confidence: 99%